2022
DOI: 10.3390/ma15175865
|View full text |Cite
|
Sign up to set email alerts
|

Crushing Characteristics of Coarse Aggregates for Asphalt Mixtures under Simulated Laboratory Compaction Loads and Repeated Traffic Loads

Abstract: The crushing characteristics of coarse aggregates for asphalt concrete were investigated under static and dynamic aggregate crushing value tests (ACVTs). The effect of various compaction loads was also examined by using a Marshall hammer, gyratory compactor and steel roller. Six types of coarse aggregates were tested, including basalt aggregate, steel slag, limestone aggregate, marble aggregate, recycled concrete aggregate and slightly weathered limestone aggregate. Test results indicate that static ACVT faile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In this regard, Liu et al (2022) [107] demonstrated that the interlocking of the lithic skeleton could be significantly promoted when traditional coarse aggregates are entirely replaced with steel slags. Moreover, steel slag is reported to have a strong crushing resistance thanks to its physical properties (comparable with that of conventional basalt aggregate), which reflects in reduced risks of particle breaking during the field compaction of the asphalt mixes [108].…”
Section: Physiscal Characteristicsmentioning
confidence: 99%
“…In this regard, Liu et al (2022) [107] demonstrated that the interlocking of the lithic skeleton could be significantly promoted when traditional coarse aggregates are entirely replaced with steel slags. Moreover, steel slag is reported to have a strong crushing resistance thanks to its physical properties (comparable with that of conventional basalt aggregate), which reflects in reduced risks of particle breaking during the field compaction of the asphalt mixes [108].…”
Section: Physiscal Characteristicsmentioning
confidence: 99%